Reforming Family Court: Getting It Right Between Rhetoric and Reality - Jane M. Spinak (Washington University Journal of Law & Policy, 2009)
What do we say about the reform work we do, and to what degree is what we say accurate? How does the way in which we talk about family court reform implicate our analysis of what we are achieving? How does our place or role within the system affect our perceptions of reform? What limits our willingness and ability to apply rigorous evaluative techniques to determine whether we are reaching our goals? And if we are failing, can we acknowledge failure and learn from it? Answering these questions may lead to a better understanding of why family court reform is stuck between rhetoric and reality.
Keywords: Domestic relations courts; Judicial reform; Court administration; Family courts; Judicial process; New York